Penerapan Teknologi QR-Code Untuk Absensi Mahasiswa Prodi Teknologi Informasi Politeknik Negeri Ketapang - Indah Pradasari, Novi; Muhammad, Ar-Razy; Sagita, Dela; Supiarti, Nini (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Digital technology is the closest thing to humans in this era, more and more human life activities ranging from entertainment content, shopping activities and even learning activities have used digital technology. So using the help of technology allows us to obtain all kinds of information quickly and surely. The role of technology has also changed many activities in the world of education, such as in the process of teaching and learning activities, lecturers or teachers can teach without having to be in the same place, but by going online using information technology. Another example is the academic administration process has also used a lot of technology, so that the process of processing grades, such as study results cards and attendance is carried out using information systems. The purpose of this research is to build an attendance system using Qr-Code which is built using the Laravel framework with the agile model software development method. The results of this study are in the form of a web-based attendance information system using Qr-Code, so that this system makes it easier for lecturers to monitor their students as well as a way to prevent cheating by students.